'No chance to speak': developing a pedagogical response to turn-taking problems. Issue 2 (15th March 2021) - Ryan, Jonathon; Forrest, Leslie
ABSTRACT : Of the major aspects of language use, perhaps the least frequently taught and the least understood by teachers is the system of turn-taking Wong and Waring [2010. Conversation Analysis and Second Language Pedagogy: A Guide for ESL/EFL Teachers . New York: Routledge]. For second language learners, this may be an important contributing factor to the experience of being unable to detect and seize opportunities to speak in multi-party talk, and more generally to the low participation rates of some learners to group discussions involving native speakers. However, pedagogical interventions are hampered by the lack of commercially available turn-taking resources. To address this issue, the authors initiated an 18-month action research project with the aim of developing relevant tasks and materials and exploring the reactions of learners to such unfamiliar content. Both teachers and learners recorded their reflections, and these responses were used to refine the activities and inform the creation of new ones. Among the challenges faced were the lack of learner awareness of turn-taking as an issue, the unconventional nature of relevant tasks, and the necessary focus on contingent possibilities rather than firm rules. The findings discuss the navigation of such issues, indicating both the teachability of turn-taking and general student receptiveness to turn-taking-focused tasks as being a worthwhile use of class time.